Universities, Museums, and Communities: Strategic Perspectives - Geert Bouckaert (Transylvanian Review of Administrative Sciences, 2024)
Societies are changing as well as their major in¬stitutions such as universities and museums which are impacted by societal transformations, but also vice-versa. Universities and museums have ambi¬tions to impact changes and transformations of society. This changing interaction is dynamic and contingent and requires strong institutions.